1999
DOI: 10.1111/j.1559-1816.1999.tb02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideologies and Support for Censorship: Is It a Question of Whose Ox Is Being Gored?

Abstract: Two studies are described. one of 381 university students and the other a statewide survey of 295 adults, both of which examine the relationship between attitudinal support for censorship and political ideologies. Thc results of these studies are interpreted as challenging the view of Suedfeld, Steel, and Schmidt ( I 994) that support for censorship is a function o f both the works in question and the political ideologies ofthe respondents. In both studies we find that s~ipport for censorship is somewhat consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Using an experimental approach, Lindner and Nosek (2009) found that conservatism predicted intolerance of anti‐American speech, but liberalism did not predict intolerance of anti‐Arab speech. Their conclusion, based on their evidence that conservatism is more strongly related to political intolerance, is consistent with the correlational evidence from the extant literature they reviewed (Altemeyer, 1996; Davis & Silver, 2004; Fisher et al., 1999; Sniderman et al., 1989). We adopted Lindner and Nosek's approach of experimentally manipulating the stated position of political targets, but contrary to their findings, our study offers clear evidence that both political liberalism and conservatism predict intolerance of politically opposing targets and that such intolerance is explained by perceived threat from these targets.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Using an experimental approach, Lindner and Nosek (2009) found that conservatism predicted intolerance of anti‐American speech, but liberalism did not predict intolerance of anti‐Arab speech. Their conclusion, based on their evidence that conservatism is more strongly related to political intolerance, is consistent with the correlational evidence from the extant literature they reviewed (Altemeyer, 1996; Davis & Silver, 2004; Fisher et al., 1999; Sniderman et al., 1989). We adopted Lindner and Nosek's approach of experimentally manipulating the stated position of political targets, but contrary to their findings, our study offers clear evidence that both political liberalism and conservatism predict intolerance of politically opposing targets and that such intolerance is explained by perceived threat from these targets.…”
Section: Discussionsupporting
confidence: 72%
“…In their article, they reviewed the literature on the relationship between conservatism and political tolerance—that is, the extent to which people extend civil liberties and rights to groups or individuals with whom they disagree (Marcus, Sullivan, Theiss‐Morse, & Wood, 1995; Sullivan, Marcus, Feldman, & Piereson, 1981). While Lindner and Nosek cited some political commentators who argue that political censorship occurs on both the right and left (Hentoff, 1992; Will, 2002), the empirical evidence reviewed implicates political conservatism as a stronger predictor of political intolerance (Altemeyer, 1996; Davis & Silver, 2004; Fisher et al., 1999; Sniderman, Tetlock, Glaser, Green, & Hout, 1989). To address this issue experimentally, Lindner and Nosek (2009) manipulated the content of an individual's speech act.…”
mentioning
confidence: 99%
“…Other research also supports this claim. For example, political conservatism predicts greater willingness to censor both politically correct and incorrect content (Altemeyer, 1996; Fisher et al., 1999). Recent research on post‐9/11 political differences in Americans' support for civil liberties over security found that liberals were less willing to trade speech tolerance for increased security (Davis & Silver, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Altemeyer (1996) found that among both college students and legislators, “even when the issues were raised in the context of leftist censoring, rightists wanted censorship more than anyone else” (pp. 230–233; see also Fisher et al., 1999).…”
Section: Political Tolerance and Censorshipmentioning
confidence: 94%
See 1 more Smart Citation